Regulatory electron transport pathways of photosynthesis in cyanobacteria and microalgae: Recent advances and biotechnological prospects - Nikkanen Lauri; Solymosi Daniel; Jokel Martina; Allahverdiyeva Yagut (WILEY, 2022)
Cyanobacteria and microalgae perform oxygenic photosynthesis where light energy is harnessed to split water into oxygen and protons. This process releases electrons that are used by the photosynthetic electron transport chain to form reducing equivalents that provide energy for the cell metabolism. Constant changes in environmental conditions, such as light availability, temperature, and access to nutrients, create the need to balance the photochemical reactions and the metabolic demands of the cell. Thus, cyanobacteria and microalgae evolved several auxiliary electron transport (AET) pathways to disperse the potentially harmful over-supply of absorbed energy. AET pathways are comprised of electron sinks, e.g. flavodiiron proteins (FDPs) or other terminal oxidases, and pathways that recycle electrons around photosystem I, like NADPH-dehydrogenase-like complexes (NDH) or the ferredoxin-plastoquinone reductase (FQR). Under controlled conditions the need for these AET pathways is decreased and AET can even be energetically wasteful. Therefore, redirecting photosynthetic reducing equivalents to biotechnologically useful reactions, catalyzed by i.e. innate hydrogenases or heterologous enzymes, offers novel possibilities to apply photosynthesis research.